Child Custody Due to Wife’s Mental Disorder: A Maqashid Shariah Perspective Analysis - Villiana, Charly Octa; Fauzi, Mohammad Yasir; Hermanto, Agus (Al-Risalah, 2025)
This study aims to explore the underlying considerations of the panel of judges in delivering a verdict on the case Number 381/Pdt.G/2024/PA.Tnk and to review it from the perspective of maqashid shariah. This research uses a qualitative method, is descriptive-analytical in nature, and employs a library research approach. The data is analyzed using the perspective maqashid shariah to assess the welfare of the child if raised by the father. The findings of this study reveal that the judge decided to grant hadhanah (custody) to the plaintiff (husband) until the children reach adulthood. One of the key considerations for this decision was the concern for the health and safety of the children while they were under the care of the defendant (wife), who was diagnosed with a mental disorder, rendering her unable to properly care for and educate the children. From the perspective of maqashid shariah, the transfer of custody to the plaintiff (husband) is clearly intended for the benefit of the children. This falls under the maqashid sharia daruriyyat (essential objectives), which include the preservation of religion, life, intellect, lineage, and wealth of the child. The analysis through the lens of maqashid sharia makes a significant academic contribution by framing the decision within the context of preserving the essential values (daruriyyat), namely the protection of the child’s religion, life, intellect, lineage, and wealth. This approach enriches the study of Islamic family law by affirming the relevance of maqashid shariah principles in the legal decision-making process, thus offering a more comprehensive perspective.